Positive electrode safety coating slurry, preparation method and safety layer

The safety coating slurry is prepared by modifying in-situ composite materials and in-situ composite methods, which solves the problem of difficulty in uniform dispersion of powder particles in the lithium-ion battery safety coating slurry, achieving a denser coating and higher Safety performance.

CN119361654APending Publication Date: 2025-01-24惠州赣锋锂电科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411576058.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

During the preparation process, the powder particles are difficult to disperse evenly during the existing lithium-ion battery safety coating slurry, resulting in agglomeration and missed coating problems, affecting the safety performance and performance stability of the battery.

Method used

Adopt modified in situ composite materials, including the active substances and oxides after modified modification, to react in the liquid phase through the original composite method to form a multi -phase coupling structure, combined with the appropriate solvent and mixing process to prepare dense safety coating Purch, reduce the phenomenon of reunion and improve the tightness of the coating.

Benefits of technology

It effectively alleviates the problem of coating leakage, improves the pass rate of acupuncture and heavy object impact tests of the battery core, enhances the cured strength, stiffness, high temperature resistance and oxidation resistance of the safety layer, and improves the overall safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361654A_ABST
    Figure CN119361654A_ABST
Patent Text Reader

Abstract

The invention discloses lithium ion battery cell positive electrode safety coating slurry, a preparation method and a safety layer, the safety coating slurry comprises a safety coating and a solvent, the safety coating comprises an in-situ composite material, a conductive agent, a solid electrolyte and a binder, and the in-situ composite material accounts for 50-99% of the total mass of the safety coating; the conductive agent accounts for 0.1-10% of the total mass of the safe coating; the solid electrolyte accounts for 0.1-25% of the total mass of the safe coating; and the binder accounts for 0.1-10% of the total mass of the safe coating. According to the lithium ion cell positive electrode safety coating slurry and the safety layer, the in-situ composite material in the slurry is obtained through in-situ formation and has different particle size structures, the phenomenon of powder particle aggregation in the preparation process of the safety coating slurry is reduced, the slurry is dispersed more uniformly, and the service life of the slurry is prolonged. And the needling passing rate and the heavy object impact resistance of the battery cell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium-ion battery cells, and in particular to a lithium-ion battery cell positive electrode safety coating slurry and a preparation method thereof, and a safety layer. Background Art

[0002] The potential safety hazards of lithium-ion batteries during use mainly include combustion and explosion. Falling into water, being stabbed by sharp objects, falling from heights, and a sharp increase in ambient temperature during daily use can cause structural damage to the battery components, thereby triggering a rapid exothermic reaction and deflagration of the lithium-ion battery. In the prior art, in order to improve the safety of lithium-ion batteries, a safety coating is added to the electrode, that is, a safety coating slurry is coated on the surface of the electrode. The safety coating is a thin film layer composed of one or more metal oxides and various additives (including binders, dispersants, etc.). Coating the safety coating on the electrode surface can effectively improve the safety performance of lithium-ion batteries, including preventing fire and explosion when mechanical external forces such as needle puncture and heavy object impact damage the battery cell.

[0003] The safety coating slurry in the prior art is formed by additionally introducing inorganic non-metallic ceramic materials and uniformly mixing them with active substances, conductive agents and binders through the adjustment of the stirring process. The prepared slurry is a non-Newtonian fluid, and the powder particles are difficult to disperse completely and evenly in the solvent, and are prone to agglomeration. By adding dispersants and optimizing the stirring process equipment, the agglomeration of the safety coating slurry can be reduced, but the phenomenon of missing coating can still be found at the microscopic level. Although it can more effectively improve the safety performance of lithium-ion batteries than current collectors without safety coating, the pass rate of safety tests such as needle puncture and heavy object impact is still not high.

[0004] Coating a safety coating on the surface of the positive electrode current collector of a lithium-ion battery increases the transmission path of electrons and lithium ions, making the safety battery cell have a greater impedance than ordinary battery cells, reducing the ED performance of the battery cell; it also reduces the electrode peeling force, making it easier for the active material and the foil to peel off, affecting the performance of the lithium-ion battery. Summary of the invention

[0005] In order to solve the problem of powder particles in the preparation process of the safety coating slurry, the present invention proposes a lithium ion battery positive electrode safety coating slurry and a preparation method, and a safety layer. The composite degree of the material is improved by modification, the agglomeration phenomenon in the preparation process of the safety coating slurry is reduced, the density of the coating is improved, the problem of coating leakage is effectively alleviated, the influence on the positive electrode peeling force is reduced, and the strength, stiffness, high temperature resistance and oxidation resistance of the safety layer after curing are improved, thereby improving the pass rate of the battery cell needle puncture and heavy object impact test.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A lithium-ion battery positive electrode safety coating slurry comprises a safety coating and a solvent, wherein the safety coating comprises an in-situ composite material, a conductive agent, a solid electrolyte and a binder, wherein the in-situ composite material accounts for 50-99% of the total mass of the safety coating; the conductive agent accounts for 0.1-10% of the total mass of the safety coating; the solid electrolyte accounts for 0.1%-25% of the total mass of the safety coating, and the binder accounts for 0.1-10% of the total mass of the safety coating.

[0007] Furthermore, the in-situ composite material includes modified active substances and oxides.

[0008] Furthermore, the solvent includes at least one of N-methylpyrrolidone, N-ethylpyrrolidone, acetone, and an ethanol-xylene mixed solution.

[0009] Further, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, Ketjen black, nano carbon fibers, and graphene; and / or The solid electrolyte comprises at least one of lithium titanate, lithium aluminum titanium phosphate, lithium lanthanum titanate, lithium lanthanum tantalate, lithium aluminum germanium phosphate, lithium lanthanum zirconium oxide, and lanthanum zirconium aluminum lithium oxide in different stoichiometric ratios; and / or The binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyethylene oxide and alginate.

[0010] Furthermore, the oxide includes at least one of magnesium oxide, manganese oxide, aluminum oxide, tin oxide, zinc oxide, calcium oxide, strontium oxide, barium oxide, yttrium oxide, lanthanum oxide, cerium oxide, praseodymium oxide, neodymium oxide, praseodymium oxide, samarium oxide, gadolinium oxide, ferric oxide, scandium oxide, silicon oxide, and antimony oxide.

[0011] The method for preparing the safety coating slurry comprises the following steps: Step 1): Take an active material precursor solution, add an excess of at least one of a metal salt solution, a metalloid salt solution, and a rare earth metal salt solution, stir evenly, and obtain a mixed solution I; Wherein: the normal molar ratio of active material precursor solution, (metal salt solution, metalloid salt solution, rare earth metal salt solution) and complexing agent solution is 1: (0.0001~0.05): (0.0001~0.05), and the excess addition amount is 0.1~5% of the normal amount, preferably 1~3%.

[0012] Preferably, at least two of the metal salt solution, metalloid salt solution, and rare earth metal salt solution are added in a mass ratio of (0-95%): (0-95%): (0-95%), wherein the mass ratios of the two are not 0, and the sum of the three mass ratios is 100%. For example, the mass ratio of the metal salt solution, metalloid salt solution, and rare earth metal salt solution can be 0:20:80, 10:90:0, 50:0:50, 75:0:25, 95:0:5, 20:40:40, 33:33:34, 12:50:38, 10:2:88, and the specific ratio is not limited.

[0013] Further, the active material includes at least one of lithium cobalt oxide, lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium manganese oxide; and / or The metal element includes at least one of magnesium, calcium, strontium, barium, manganese, aluminum, tin and zinc; and / or The metalloid element includes at least one of silicon and antimony; and / or The rare earth metal element includes at least one of scandium, yttrium, lanthanum, cerium, praseodymium, neodymium, samarium, gadolinium and ytterbium.

[0014] Step 2): Take a complexing agent solution, add it to the mixed solution I, stir evenly, and obtain a mixed solution II. The complexing agent solution includes one of sodium nitrilotriacetate, ethylenediaminetetraacetate, and diethylenetriaminepentacarboxylate.

[0015] Step 3): The pH value of the mixed solution II is adjusted to a range of 7 to 10, preferably 8 to 9; an alkaline environment is conducive to the dissolution of the material. The heating temperature is set between 60 and 100°C, and the water is heated until it is partially or completely evaporated, preferably completely evaporated, to obtain a gel.

[0016] Step 4): Place the gel in a drying device for drying, the temperature is set between 100 and 500°C, preferably 200 to 400°C; the drying time is set between 1 and 15 hours, preferably 5 to 10 hours; and a fluffy precursor powder is obtained.

[0017] Preferably, a precursor powder grinding step is added to grind the powder with large lumps or particles to a size of not less than 20 mesh, preferably 20-140 mesh, so that the calcination is more complete and the calcination time is shortened.

[0018] Optionally, the precursor powder can be ground using a ball mill with a rotation speed controlled at 100-500rpm / min; the use of a ball mill can refine the precursor powder and improve the uniformity of the distribution of each component material. If the rotation speed is lower than 100rpm / min, the distribution consistency of each component material is poor, resulting in insufficient subsequent high-temperature calcination reaction and easy formation of impurities. If the rotation speed is greater than 500rpm / min, it is easy to re-crush the component materials, and the particle size of the product powder is too small to meet the process requirements.

[0019] Step 5): Place the precursor powder in a heating furnace and set the calcination temperature between 700 and 1000°C. If the sintering temperature is less than 700°C, the mixture will not be sintered completely and the material will not meet the performance requirements. If the sintering temperature is greater than 1000°C, the product will decompose again. Preferably, the calcination temperature is 800 to 900°C.

[0020] The calcination time is 2 to 15 hours. If the calcination time is less than 2 hours, the reaction between the raw material components is not sufficient, and if it exceeds 15 hours, the compound will be over-sintered and lose its original structure and properties. Preferably, the calcination time is 5 to 10 hours.

[0021] Excess doping elements react with oxygen during high-temperature calcination to generate at least one of metal oxides, metalloid oxides, and rare earth metal oxides; the oxide and active material generation processes occur simultaneously to form an in-situ mixed oxide and active material composite.

[0022] Step 6): Mix the conductive agent, solid electrolyte, binder and the in-situ composite material obtained in step 5) in proportion, add solvent, wherein the solid content is 10-60%, preferably 20-50%; stir evenly to prepare a safety coating slurry, the viscosity of the slurry is in the range of 50-1000mPa·s, preferably 100-500mPa·s.

[0023] In order to make the powder mixing more uniform, preferably, this step can be performed as follows: Step 601): Take a conductive agent, a solid electrolyte, a binder and the in-situ composite material obtained in step 5) according to a mass ratio, and prepare an organic solvent; Step 602): The conductive agent prepared in S1 is divided into three parts, namely conductive agent 1, conductive agent 2 and conductive agent 3, the mass ratio of conductive agent 1, conductive agent 2 and conductive agent 3 is 10-50%:10-50%:10-80%, and the sum of the mass ratios is 100%. For example, the mass ratios of conductive agent 1, conductive agent 2 and conductive agent 3 can be 10%:10%:80%, 21%:31%:48%, 35%:35%:30%, 33%:34%:33%, 40%:10%:50%, 50%:20%:30%, 12%:50%:38%, and there is no specific limitation.

[0024] The solid electrolyte is divided into two parts, namely solid electrolyte 1 and solid electrolyte 2, wherein the mass ratio of solid electrolyte 1 to solid electrolyte 2 is 10-80%:30-90%, and the sum of the mass ratios is 100%. For example, the mass ratio of solid electrolyte 1 to solid electrolyte 2 can be 10%:90%, 15%:85%, 30%:70%, 50%:50%, 51%:49%, 64%:36%, 75%:25%, 80%:20%, and the specific ratio is not limited.

[0025] Step 603): Add the conductive agent 1, the in-situ composite material, and the solid electrolyte 1 into the solvent and stir evenly to obtain a premix 1; Step 604): Add conductive agent 2 and solid electrolyte 2 to premix 1, and stir evenly to obtain premix 2; Step 605): Add conductive agent 3 and binder to premix 2, stir evenly, and prepare safety coating slurry.

[0026] The safety coating slurry is evenly coated on the surface of the positive electrode active material layer or the positive electrode current collector by roller coating or spraying and dried to obtain a safety coating, wherein the thickness of the safety coating is 1 to 14 μm, preferably 3 to 9 μm. If the coating is too thick, the energy density of the battery cell will be reduced and the weight of the battery cell will be increased. If the coating is too thin, it is easy to leak under the microscopic condition.

[0027] Specifically, the positive electrode active material layer is a positive electrode current collector coated with active material; and the positive electrode current collector is a metal foil.

[0028] In summary, the beneficial effects of the present invention are: 1) The in-situ composite material in the safety coating slurry is obtained by in-situ formation. The particles with a particle size range of 200~900nm are obtained by high-temperature calcination of the gel, which directly reaches the particle size range required for the preparation of the safety coating, without the need for secondary processing such as increasing or reducing the particle size. In addition, a variety of different particle size structures make the powder mixing more uniform, reducing the phenomenon of powder particle agglomeration during the slurry preparation process. The prepared safety layer effectively alleviates the occurrence of missing coating, the coating is denser, and the pass rate of the needle test is increased.

[0029] 2) In-situ composite materials are modified mixtures of active substances and oxides. Through the in-situ composite method, two or more materials are reacted in the liquid phase to form a multi-phase coupled structure, which can disperse stress and increase the strength and stiffness of the material, thereby improving the pass rate of the heavy object impact test of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] FIG1 is a particle size distribution diagram of the in-situ composite material prepared by the method of the present invention; FIG2 is a diagram of a positive electrode sheet with a safety layer prepared in Example 1; FIG3 is a 100-fold magnified image of the positive electrode sheet with a safety layer prepared in Example 1; FIG4 is a 100-fold magnified image of the positive electrode sheet with a safety layer prepared in Comparative Example 1. DETAILED DESCRIPTION

[0031] The following is a preferred embodiment of the present invention. It should be noted that a person skilled in the art may make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention. Example

[0032] In-situ composite material preparation Prepare a lithium cobalt oxide precursor solution, a magnesium salt solution and a complexing agent solution in a molar ratio of 1:0.0303:0.01. Mix the lithium cobalt oxide precursor solution and the magnesium salt solution, stir evenly, and obtain a mixed solution I.

[0033] Add the complexing agent solution to the mixed solution I, stir evenly at room temperature, and obtain a mixed solution II.

[0034] Add ammonia water to the mixed solution II to adjust the pH value to 8, and heat until the water evaporates completely to obtain a gel. Through the in-situ composite method, the two materials react in the liquid phase to form a multiphase coupled structure, which can disperse stress and increase the strength and stiffness of the material.

[0035] The gel was placed in an oven to dry, the oven temperature was set to 300°C, and the baking time was set to 8 hours. After baking, the gel was taken out to obtain a fluffy precursor powder.

[0036] The powder is placed in a grinding device and ground to a particle size of 20 mesh or more.

[0037] The ground powder is placed in a container, the container is placed in a heating furnace, the calcination temperature is set to 800°C, and the calcination time is set to 5 hours; after the calcination is completed, it is cooled to room temperature in air to obtain an in-situ composite material, that is, modified active substance and oxide mixture particles. In the method of the present invention, there is no requirement for the cooling method and environment, such as in flowing air to accelerate the cooling speed.

[0038] As shown in Figure 1, the particle size range is mainly between 200 and 900 nm, reaching the particle size range required for the preparation of safety coatings, and no secondary processing such as increasing or reducing the particle size is required. The smaller the particle size, the more uniform the coating and the less likely it is to leak, but the more likely it is to agglomerate; when the particle size is less than 100 nm, the prepared slurry is prone to sedimentation and has poor stability. If the particle size is too large, it is difficult to coat evenly, and it is easy to leak after coating. During the slurry preparation process, the powder particles have a variety of different particle size structures. Compared with particle size structures with the same or similar particle size, when stirred in the solvent, there is less agglomeration, and the prepared safety layer has a denser coating.

[0039] Preparation of safety coating slurry Take the in-situ composite material, prepare carbon nanotubes, lithium aluminum titanium phosphate, polyvinylidene fluoride, and prepare a solvent N-methylpyrrolidone, wherein the mass ratio of the in-situ composite material, carbon nanotubes, lithium aluminum titanium phosphate, and polyvinylidene fluoride is 96:1:2:1.

[0040] The carbon nanotubes are divided into three parts, namely carbon nanotube 1, carbon nanotube 2 and carbon nanotube 3, wherein the mass ratio of carbon nanotube 1, carbon nanotube 2 and carbon nanotube 3 is 25%: 25%: 50%; The lithium aluminum titanium phosphate is divided into two parts, namely lithium aluminum titanium phosphate 1 and lithium aluminum titanium phosphate 2, wherein the mass ratio of lithium aluminum titanium phosphate 1 to lithium aluminum titanium phosphate 2 is 40%:60%.

[0041] Adding carbon nanotubes 1, in-situ composite materials, and lithium aluminum titanium phosphate 1 into N-methylpyrrolidone, and stirring evenly to obtain a premix 1; Add carbon nanotubes 2 and lithium aluminum titanium phosphate 2 to premix 1, and stir evenly to obtain premix 2; Add carbon nanotubes 3 and polyvinylidene fluoride to the premix 2, stir evenly, and prepare a safety coating slurry with a solid content of 30%.

[0042] Preparation of security layer The safety coating slurry was uniformly coated on the surface of the aluminum foil by continuous gravure roller coating and dried to obtain a positive electrode with a safety layer, wherein the thickness of the safety layer was 3 μm. The surface peeling force of the positive electrode was tested, as shown in Table 1.

[0043] The prepared positive electrode with a safety layer is shown in FIG2 , and no coating is missed by naked eye observation; under a 100x viewing microscope, as shown in FIG3 , the particle size of the missed coating is less than 10 um.

[0044] Preparation of battery cells The positive electrode with the safety layer is stacked and wound in sequence with the isolation film and the negative electrode sheet to obtain an electrode assembly; the electrode assembly is placed in an outer package, and an electrolyte is added. After packaging, standing, forming, aging and other processes, a battery cell is obtained.

[0045] Acupuncture test Fully charge the battery to be tested and let it stand for 24 hours, then place it in the middle of the explosion-proof box, with the center of the largest surface of the battery aligned directly below the probe, close and lock the explosion-proof box, and use a 3mm diameter probe at a speed of 40mm / s to completely pierce the battery at one time, and pull out the needle after 10 seconds. From the time the needle touches the battery to the time the surface temperature of the battery naturally drops below 50°C, the battery should not smoke, catch fire, or explode, which is considered qualified.

[0046] The results of the acupuncture test are shown in Table 1.

[0047] Heavy object impact test Place the battery cell to be tested into the battery heavy object impact test equipment, and drop an object weighing 9.1Kg±0.46Kg from a height of 610mm±25mm to impact the battery cell, and leave it to stand for 6 hours. The battery cell does not catch fire or explode, which is considered as the qualified standard.

[0048] The results of the heavy object impact test are shown in Table 1.

[0049] Comparative Example 1 Preparation of safety coating slurry The preparation method of the safety coating slurry in Example 1 is different in that the "in-situ composite material" is replaced with "lithium cobalt oxide, magnesium oxide" solid particles purchased on the market; and a dispersant is additionally added during stirring to alleviate the agglomeration problem. The particle size of the lithium cobalt oxide and magnesium oxide solid particles is in the range of 200-900nm; the molar ratio of lithium cobalt oxide to magnesium oxide is 1:0.03.

[0050] Preparation of security layer The preparation method of the safety layer in Example 1 is different in that the method is applied twice. Since the coating is missed by the naked eye after one coating, the thickness of the safety layer obtained after two coatings is 6 μm. The positive electrode with the safety layer is not missed by the naked eye. Under a 100-fold viewing microscope, as shown in FIG4, there are 31 places where the particle size of the missed coating is greater than 10 um, and there is 1 place where the particle size of the missed coating is greater than 20 um. The size marks in the figure are representatives of the selected missed coating particle sizes of different gradients above 10 um.

[0051] Preparation of battery cells The preparation method of the battery cell in Example 1 was followed.

[0052] Acupuncture test According to the acupuncture test method and judgment criteria in Example 1, the test results are shown in Table 1.

[0053] Heavy object impact test According to the heavy object impact test method and judgment criteria in Example 1, the test results are shown in Table 1. Example

[0054] The specific preparation process is the same as that of Example 1, except that the "magnesium salt solution" for preparing the in-situ composite material is replaced with "magnesium salt solution, silicon salt solution", and the molar ratio of the body solution, oxide solution and complexing agent solution of the mixed solution I remains unchanged, that is, the molar ratio of the lithium cobalt oxide precursor solution, (magnesium salt solution, silicon salt solution) and complexing agent solution is 1:0.0303:0.01. The mass ratio of the magnesium salt solution to the silicon salt solution is 50%:50%. Example

[0055] The specific preparation process is the same as that of Example 1, except that the "magnesium salt solution" for preparing the in-situ composite material is replaced with "magnesium salt solution, silicon salt solution, lanthanum salt solution", and the molar ratio of the body solution, oxide solution and complexing agent solution of the mixed solution I remains unchanged, that is, the molar ratio of the lithium cobalt oxide precursor solution, (magnesium salt solution, silicon salt solution, lanthanum salt solution) and complexing agent solution is 1:0.0303:0.01. The mass ratio of the magnesium salt solution, the silicon salt solution and the lanthanum salt solution is 33%:33%:34%.

[0056] The more types of metal salts, metalloid salt solutions, rare earth metal solutions and precursor solutions reacting in the liquid phase, the more coupled structural phases there are, the better the stress dispersion effect is, and the higher the strength and stiffness of the material. As shown in Table 1, compared with Example 2 and Example 1, Example 3 has better resistance to heavy object impact.

[0057] Comparative Example 2 The preparation process of the safety coating slurry is the same as that of Comparative Example 1, except that the "lithium cobalt oxide and magnesium oxide" used to prepare the safety coating slurry is replaced with "lithium cobalt oxide, magnesium oxide, silicon oxide, and lanthanum oxide". The molar ratio of lithium cobalt oxide to (magnesium oxide, silicon oxide, and lanthanum oxide) is 1:0.03, and the mass ratio of magnesium oxide, silicon oxide, and lanthanum oxide is 33%:33%:34%.

[0058] The preparation process of the security layer is the same as that of Comparative Example 1, except that "the thickness of the security layer is 6 μm" is replaced by "the thickness of the security layer is 12 μm". Example

[0059] The specific preparation process is the same as that of Example 3, except that in the preparation of the security layer, "the thickness of the security layer is 3 μm" is replaced by "the thickness of the security layer is 4 μm". Example

[0060] The specific preparation process is the same as that of Example 3, except that in the preparation of the security layer, "the thickness of the security layer is 3 μm" is replaced by "the thickness of the security layer is 6 μm".

[0061] The specific preparation process is the same as that of Example 3, except that in the preparation of the safety layer, "the thickness of the safety layer is 3 μm" is replaced by "the thickness of the safety layer is 9 μm". The thicker the safety coating, the higher the needle puncture rate, but it will reduce the ED performance of the battery.

[0062] Comparative Example 3 Lithium-ion battery prepared with positive electrode without safety coating.

[0063] Table 1 Stripping force test of positive electrodes prepared in Examples 1-6 and Comparative Examples 1-3, and safety performance test of battery cells From the results in Table 1, it can be seen that the embodiments of the method of the present invention have the following effects: 1) The safety layer prepared by the method of the present invention effectively alleviates the occurrence of coating leakage. Under the condition of the same coating thickness, the prepared battery cell has a higher pass rate in the needle puncture test.

[0064] 2) The safety layer prepared by the method of the present invention has little effect on the peeling force compared with the comparative example 3 without the safety coating; the positive electrode prepared by the method of the present invention has a greater peeling force than the comparative examples 1 and 2. The lower the peeling force, the easier it is for the active material to be peeled off from the current collector, thereby reducing the stability of the long-term cycle of the battery cell.

[0065] 3) The safety layer prepared by the method of the present invention can effectively improve the heavy object impact resistance of the battery cell. The thicker the safety coating is, the better the heavy object impact resistance is.

[0066] 4) Adding a coating will reduce the ED performance of the battery cell. The thicker the coating, the greater the impact. The safety coating prepared by the method of the present invention has little impact on the ED performance of the battery cell. Taking into account the needle puncture pass rate and heavy impact resistance, the further preferred range of the thickness of the safety coating of the present invention is 3~6μm.

[0067] The above-mentioned implementation modes are for explanation of the present invention rather than limitation of the present invention. It can be understood that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A lithium-ion battery positive electrode safety coating slurry, comprising a safety coating and a solvent, characterized in that: The safety coating comprises an in-situ composite material, a conductive agent, a solid electrolyte and a binder, wherein the in-situ composite material accounts for 50-99% of the total mass of the safety coating; the conductive agent accounts for 0.1-10% of the total mass of the safety coating; the solid electrolyte accounts for 0.1%-25% of the total mass of the safety coating; and the binder accounts for 0.1-10% of the total mass of the safety coating.

2. The safety coating slurry according to claim 1, characterized in that: The in-situ composite material comprises modified active substances and oxides.

3. The safety coating slurry according to claim 1, wherein the solvent comprises at least one of N-methylpyrrolidone, N-ethylpyrrolidone, acetone, and an ethanol-xylene mixed solution.

4. The safety coating slurry according to claim 1, wherein the conductive agent comprises at least one of conductive carbon black, carbon nanotubes, Ketjen black, nano carbon fibers, and graphene; and / or The solid electrolyte comprises at least one of lithium titanate, lithium aluminum titanium phosphate, lithium lanthanum titanate, lithium lanthanum tantalate, lithium aluminum germanium phosphate, lithium lanthanum zirconium oxide, and lanthanum zirconium aluminum lithium oxide in different stoichiometric ratios; and / or The binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyethylene oxide and alginate.

5. The safety coating slurry according to claim 1, characterized in that: The solid content of the slurry is 10-60%.

6. The safety coating slurry according to claim 2, characterized in that: The oxide includes at least one of magnesium oxide, manganese oxide, aluminum oxide, tin oxide, zinc oxide, calcium oxide, strontium oxide, barium oxide, yttrium oxide, lanthanum oxide, cerium oxide, praseodymium oxide, neodymium oxide, praseodymium oxide, samarium oxide, gadolinium oxide, ferric oxide, scandium oxide, silicon oxide, and antimony oxide.

7. A method for preparing a safety coating slurry, characterized in that: The following steps are included: Step 1): Take an active material precursor solution, add an excess of at least one of a metal salt solution, a metalloid salt solution, and a rare earth metal salt solution, stir evenly, and obtain a mixed solution I; Step 2) taking a complexing agent solution, adding it to the mixed solution I, stirring evenly, and obtaining a mixed solution II; Step 3) adjusting the pH value of the mixed solution II to alkaline, heating until the water evaporates partially or completely, and obtaining a gel; Step 4) drying the gel at high temperature to obtain a fluffy precursor powder; Step 5) calcining the precursor powder at a high temperature in air to obtain a modified active substance and oxide mixture, namely the in-situ composite material; Step 6) The in-situ composite material obtained in step 5) is mixed with a conductive agent, a solid electrolyte and a binder, added into a solvent, and stirred evenly to obtain a safety coating slurry.

8. The preparation method according to claim 7, characterized in that: The active material in step 1) includes at least one of lithium cobalt oxide, lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium manganese oxide; and / or The metal element includes at least one of magnesium, calcium, strontium, barium, manganese, aluminum, tin and zinc; and / or The metalloid element includes at least one of silicon and antimony; and / or The rare earth metal element includes at least one of scandium, yttrium, lanthanum, cerium, praseodymium, neodymium, samarium, gadolinium and ytterbium.

9. The preparation method according to claim 7, characterized in that: The complexing agent solution in step 2) includes one of sodium nitrilotriacetate, ethylenediaminetetraacetate, and diethylenetriaminepentacarboxylate.

10. The preparation method according to claim 7, characterized in that: The pH value in step 3) is controlled within the range of 7 to 10, and the heating temperature is between 60 and 100° C.; and / or The drying temperature in step 4) is between 100 and 500° C., and the drying time is between 1 and 15 hours; and / or The calcination temperature in step 5) is 700-1000°C, and the calcination time is 2-15 hours.

11. The preparation method according to claim 7, characterized in that: The normal molar ratio of the active substance precursor solution, (metal salt solution, metalloid salt solution, rare earth metal salt solution) and the complexing agent solution is 1: (0.0001-0.05): (0.0001-0.05); and / or The excessive addition amount is 0.1-5% of the normal amount.

12. A lithium-ion battery positive electrode safety layer, characterized in that: The safety coating slurry according to any one of claims 1 to 6 is uniformly coated on the surface of the positive electrode active material layer or the surface of the positive electrode current collector.